Evaluation of four primer sets for analysis of comammox communities in black soils - Bai, Xin; Hu, Xiaojing; Liu, Junjie; Gu, Haidong; Jin, Jian; Liu, Xiaobing; Wang, Guanghua (Frontiers in Microbiology, 2022)
Comammox, as a newly discovered ammonia oxidizer, urgently needs highly efficient and specific primers to detect its community structure and diversity. In this study, the performance of widely used primer set Ntsp-amoA 162F/359R and newly designed primer sets comamoA F/R, CA377f/C576r, and CB377f/C576r were evaluated, for high-throughput sequencing of comammox amoA genes in natural and arable soils sampled from two locations in the black soil region of northeast China. Results showed that, compared with the primer set comamoA F/R, primers Ntsp-amoA 162F/359R had more advantages in detecting comammox operational taxonomic unit (OTU) numbers, diversity, and community structure. The primer sets CA377f/C576r and CB377f/C576r had an advantage in detecting comammox sequences with low relative abundance. In addition, the results of the phylogenetic tree and the relative abundance of dominant OTUs showed that the comammox in the black soils of northeast China was dominated by Nitrospira Clade B. Furthermore, our study found that long-term land use reduced the alpha diversity of the comammox community, but lead to the convergent evolution of community structure. The Mantel test and canonical correspondence analysis indicated that soil NO3–-N content was the most important factor affecting the community structure of comammox. Our study provided experience accumulation for the selection of comammox primers for high-throughput sequencing in the black soil of northeast China.